Aplikasi Pendaftaran Pasien Berbasis Android Pada Poli Anak Rumah Sakit Umum Andi Djemma Masamba - J Jumrani; A Apriyanto; Solmin Paembonan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2022)
This study aims to build and design an application and implement a Patient Registration Android-Application at the Pediatric Clinic of Andi Djemma Masamba General Hospital. The type of research used is descriptive qualitative research, which is a series of activities or processes to reveal the process of the system process. This research also uses the method waterfall with data collection techniques using data documentation, interviews, and observations. In planning this enlistment application, the UML (model Brought together Displaying Language) comprises of utilization case outlines, movement graphs, arrangement charts and class graphs. Design a logical database using MySQL. The software used in the design and implementation of the system uses XAMPP as a web server, PhpMySQL as a database, visual studio as a web design editor, and android studio as android design editor. Based Patient Registration Android-Application at the Children's Outpatient Clinic of Andi Djemma Masamba General Hospital includes a patient registration page, doctor's schedule, reports, and pediatric poly info. This application has been tested (test case) in order to obtain an application that runs well.